The Effect of Rice Straw Gasification Temperature on the Release and Occurrence Modes of Na and K in a Fluidized Bed - Tianyu Chen; Jun Cao; Baosheng Jin (Applied Sciences, 2017)
Rice straw gasification was carried out in a laboratory fluidized bed reactor system from 600 to 800 °C in order to well-understand the release and occurrence mode of alkali metals as a function of temperature during the gasification process. Inductively coupled plasma atomic emission spectrometry (ICP-AES) was applied to analyze the original rice straw and obtained fly ash at different temperatures. The results show that the Water-Soluble, Ammonium acetate-Soluble, Hydrochloric acid-Soluble, and Aluminosilicate Combination-Soluble modes of the Na and K contents in rice straw decreased in sequence. The content of Water-Soluble salts of Na and K accounts for more than 50%, while the content of the Aluminosilicate Combination-Soluble mode is the lowest: less than 5%. The release rate of Na appears to be consistent but nonlinear, increasing with gasification conversion ranges between 50.2% and 70.8%, from which we can deduce that temperature is not the only factor that impacts Na emission. The release of K can be divided into two stages at 700 °C. At the first stage, the release rate of K is almost invariable, ranging from 23.3% to 26%. At the second stage, the release rate increases sharply: up to 55.9%. The concentration and the proportion of the Water-Soluble, Ammonium acetate-Soluble, and Hydrochloric acid-Soluble modes of Na in fly ash decrease with a temperature increase. The release of K can be explained as follows: one path is an organic form of K converted into its gaseous phase; the other path is a soluble inorganic form of K that is volatile at a high temperature. With a temperature increase, the Aluminosilicate Combination-Soluble mode of both Na and K increases.